GRAMMATICAL ANALYSIS OF “ONE STOP ENGLISH LEARNING” TEXTBOOK GRADE 6 - Khoirun Nikmah; Ayu Fitrianingsih; Dian Ratna Puspananda (Universitas Muhammadiyah Semarang, 2022)
An English textbook is needed by the learners to study the materials presented by the teacher or learn independently. A textbook must contain fewer errors, especially in grammar, because they can confuse the students and influence the outcome of their learning process. This descriptive quantitative research is aimed at investigating the types of grammatical errors and determining whether the book is applicable or not for teaching sixth-grade students. The grammar inside the book was analyzed by Depraetere and Langford as well as Azar's theories. The data sources were derived from the sixth-grade elementary school textbook entitled